REVISITING FINANCIAL DISTRESS: THE ROLE OF AUDIT CREDIT, PROFITABILITY, AND LEVERAGE - Matusin, Ivan Suriansyah; Azzahra Rediva Ryandhana; Cicely Delfina Harahap (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2026)
Abstract This study aims to analyze the influence of audit committees, profitability, and leverage on financial distress among Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach with panel data regression and purposive sampling based on the completeness of financial statements during the observation period. Financial distress was measured using the financial distress index. At the same time, audit committees were proxied as audit credit, profitability was measured by Return on Assets (ROA), and leverage was measured using the Debt to Equity Ratio (DER). Based on the results of the Chow and Hausman test, the Fixed Effect model was selected as the best estimation model. The results showed that audit committees, profitability, and leverage did not significantly influence financial distress. This finding indicates that audit governance mechanisms, earnings performance, or capital structure do not directly determine financial distress in FMCG companies. This study emphasizes the importance of a sectoral approach to understanding the determinants of financial distress in non-cyclical industries. It provides practical implications for management and investors, emphasizing cash flow resilience and operational stability analysis over conventional financial indicators.